New Research in Dietary Supplements and Healthy Foods (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint describes the ability of some foods or natural substances extracted by plants to counteract some of the most common diseases at present, such as obesity, diabetes, intestinal inflammatory diseases, and neurodegeneration. It is well accepted that high-fat diets that are rich in saturated fats are involved in the onset and progression of obesity and its dangerous comorbidities. It is also well accepted that a balanced diet is useful to maintain a good health status and the choice of certain foods could help to counteract the onset of chronic diseases. Foods and natural substances rich in compounds with anti-inflammatory and antioxidant properties should be paid attention. Most of these foods belong to the Mediterranean Diet, and they are famous for being rich of unsaturated fatty acids, such as the oleic acid found in extra-virgin olive oil, or the omega 3 contained in fish, vitamin D and vitamin C with their high anti-oxidant capacity, and spices and nuts that can counteract inflammatory status. These substances have also anti-obesity properties, because they are able to reduce fat mass and and restore the physiological role of fat tissue. Therefore, strict adherence to this healthy diet could be enough to prevent the onset of chronic diseases linked to fatty diets or aging. The scientific data collected in this reprint could provide new insights, allowing for readers to change their own dietary habits and make more informed food choices.